The Nigerian Fourth Republic, Federalism and Party Aggregation - EGWIM, Ambose Ihekwoaba (Socialscientia: Journal of Social Sciences and Humanities, 2024)
The explanation for the number of effective parties in a political system is not primarily the institutional or ideological factors but rather the location of power in the federal system - centralized federalism builds up centralized national parties. Using Chhibber and Kollman’s postulation, this paper argues that Nigeria’s military-bequeathed centralized federalism is a significant factor leading to two dominant national parties, the PDP and the APC, and pushing other parties to emerge as a third force (the L.P.). The increased regional power in the First Republic encouraged forming regional ruling parties and minor parties with limited viability within the federating units. The force to aggregate at the centre became tremendous as power consistently shifted to the federal government. The miniaturization of the federating states enhanced the central government’s power and political parties’ appetite to control it. This heralded the birth of national parties or what can be referred to as dominant parties. As a means of capturing power at the centre, what emerged recently are ’umbrella’ and ’bounded broom’ parties representing groups and interests whose primary goal is to control the centre.